MOTIVASI BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN SEPAK BOLA PADA SEKOLAH MENENGAH ATAS NEGERI 9 PONTIANAK - Lamiri, Lamiri; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:The problem in this research is how Motivation learn dribble in game of soccer at student of class X High School State 9 Pontianak? This study aims to determine the motivation to learn to dribble in a soccer game on the students of class X High School State 9 Pontianak. Variables are the factors or symptoms observed in the research. The variables in this study is the motivation to learn in dribbling on the 9th grade students of State Senior High School 9 Pontianak. the method used in this research is descriptive method that aims to know the motivation to learn dribble in the game of football in the students of class X High School State 9 Pontianak. The form used is a survey of research that seeks to see the situation without giving treatment, and in this study. The population in this study were 318 sample students in this study using Cluster Sampling (Area Sampling) with a total of 64 students. Data collection techniques use measurement techniques. The data collection tool uses a questionnaire. Data analysis technique of data analysis technique used in this research is by questionnaire or questionnaire technique.Based on the data analysis can be seen that the motivation to learn dribbling in the game of football students in the class X High School State 9 Pontianak achieve the actual score of 5517 from the ideal score of 8192 means reaching 67.35% than it should, thus belonging to the category